A peak-strength strain energy storage index for rock burst proneness of rock materials. (May 2019) - Gong, Fengqiang; Yan, Jingyi; Li, Xibing; Luo, Song
Abstract: Judgement of rock burst proneness of rock materials is one of the basic problems in the field of rock burst research. In this study, a peak-strength strain energy storage index is proposed for estimating and classifying the rock burst proneness of rock materials. The method for determining this index is also introduced in this paper. The peak-strength strain energy storage index is defined as the ratio of the elastic strain energy density to the dissipated strain energy density corresponding to the peak compressive strength of rock specimen. In order to obtain the elastic strain energy density and the dissipated strain energy density at the peak strength, a series of single cyclic loading-unloading uniaxial compression tests on nine rock materials were conducted. The relationships between the total input energy density and the elastic strain energy density at different unloading stress levels were investigated. The results show that, for every rock material, the elastic strain energy density increases linearly with the increase of the total input energy density. Based on this linear storage energy law, the elastic & dissipated strain energy density at the peak strength can be calculated for each specimen, and the peak-strength strain energy storage index can be obtained accordingly. A new criterion for rock burst proneness of rock materials is proposed. The rock burst proneness of nine rock materials estimated with the proposed criterion agreed well with the laboratory test results.